Metabolic-Associated Fatty Liver Disease: The Influence of Oxidative Stress, Inflammation, Mitochondrial Dysfunctions, and the Role of Polyphenols - Tauil, Raissa Bulaty (2024)
Metabolic-Associated Fatty Liver Disease (MAFLD) is a clinical–pathological scenario that occurs due to the accumulation of triglycerides in hepatocytes which is considered a significant cause of liver conditions and contributes to an increased risk of death worldwide. Even though the possible causes of MAFLD can involve the interaction of genetics, hormones, and nutrition, lifestyle (diet and sedentary lifestyle) is the most influential factor in developing this condition. Polyphenols comprise many natural chemical compounds that can be helpful in managing metabolic diseases. Therefore, the aim of this review was to investigate the impact of oxidative stress, inflammation, mitochondrial dysfunction, and the role of polyphenols in managing MAFLD. Some polyphenols can reverse part of the liver damage related to inflammation, oxidative stress, or mitochondrial dysfunction, and among them are anthocyanin, baicalin, catechin, curcumin, chlorogenic acid, didymin, epigallocatechin-3-gallate, luteolin, mangiferin, puerarin, punicalagin, resveratrol, and silymarin. These compounds have actions in reducing plasma liver enzymes, body mass index, waist circumference, adipose visceral indices, lipids, glycated hemoglobin, insulin resistance, and the HOMA index. They also reduce nuclear factor-KB (NF-KB), interleukin (IL)-1β, IL-6, tumor necrosis factor-α (TNF-α), blood pressure, liver fat content, steatosis index, and fibrosis. On the other hand, they can improve HDL-c, adiponectin levels, and fibrogenesis markers. These results show that polyphenols are promising in the prevention and treatment of MAFLD.